Analisis Amonia, Hidrogen Sulfida dan Kebauan Limbah Cair Rumah Potong Hewan Kota Jambi - Jalius Jalius; Yurleni Yurleni; M. Rasyid Ridho; Fachroerrozi Hoesni; Firmansyah Firmansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the levels of ammonia and hydrogen sulfide contained in wastewater as well as the degree of odor to the environment around the Jambi City Slaughterhouse. The research design used was Randomized Block Design (RBD) with 4 sampling points as treatment, LI (cow and buffalo wastewater), L-II (swine wastewater), L-III (Mixed cow and buffalo liquid waste) , L-IV (Place of discharge of wastewater into public channels) and 4 replications. The observed variables were ammonia, hydrogen sulfide and environmental odor. Test results on the average ammonia content L-I = 124.75 ± 4.99; L-II = 60.25 ± 6.60; L-III = 108.50 ± 7.73 and L-IV = 95.50 ± 6.24. Test results on the average content of hydrogen sulfide L-I = 0.428 ± 0.08; L-II = 0.068 ± 0.10; L-III = 0.063 ± 0.09 and L-IV = 0.010 ± 0.00. The results showed that the ammonia and hydrogen sulfide content at the final outlet to the common channel decreased (P <0.01). From this study it can be concluded that the handling of Jambi City Slaughterhouse liquid waste when viewed from the ammonia and hydrogen sulfide content at the wastewater outlet to the public channels are 95.50 mg / L and 0.01 mg / L, respectively. The level of odor of the Jambi City Slaughterhouse waste was still smelled up to a distance of 178 m from the Slaughterhouse complex to community housing. Almost all respondents agreed that the level of odor that was smelled up to the level of odor, even from some respondents stated that the waste originating from Slaughterhouse was very smelly.